Endoscopic cheap optical transducers (CHOTs) for on-wing ultrasonic inspection - Ageeva, Victoria (2016)
The instrumentation and the developments presented in this thesis aim to address the challenges associated with in-service non-destructive testing of aeroengine components, imposed by severe restrictions on component accessibility.